The role of expatriates in MNCs knowledge mobilization - Mariano, Stefania; Mohamed, Mirghani; Mohiuddin, Qadir; Ghauri, Pervez N., 1948- (Emerald, 2011)
This book explores the role of expatriates in the mobilization and nurturing of knowledge between their original (parent/home) country and the MNCs host countries. This includes the management of knowledge and the tools, methods and practices that can be customized to facilitate the transfer of knowledge in MNCs settings. The text is an in-depth international compendium of theoretical and empirical studies about the role of expatriates in knowledge transfer at global levels. Thorough and comprehensive, it covers topics recognized by practitioners, academics, and researchers, yet about which very little has been published at an international level. Coverage includes: organizational culture; cross-cultural differences; globalization; cross-generational issues, technology-based sharing systems; intellectual capital management; linguistic differences; and distinctive political practices. It investigates the challenges imposed by culture, generation, tools, laws, regulations, and language, and examines the benefits of knowledge management principles that originate from different cultures, heterogeneous knowledge, and diverse intellectual capital management in global settings.
Keywords: International business enterprises.; Foreign workers.; elektronické knihy; electronic books